The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10253890.2017.1389883
|View full text |Cite
|
Sign up to set email alerts
|

Maternal behavior of the mouse dam toward pups: implications for maternal separation model of early life stress

Abstract: Maternal care is essential for an adequate pup development, as well as for the health of the dam. Exposure to stress in early stages of life can disrupt this dam-pup relationship promoting altered neurobiological and behavioral phenotypes. However, there is a lack of consensus regarding the effects of daily maternal separation (MS) on the pattern of maternal behavior. The aim of this study is to compare the patterns of maternal behavior between mice exposed to MS and controls. BALB/c mice were subjected to MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
2
26
0
4
Order By: Relevance
“…Importantly, we hypothesize brief periods of pup separation during neuroendocrine and behavioral assays in our study did not significantly contribute to our stress paradigm. Previous studies have shown brief pup separation is not a sufficient stressor to increase maternal HPA axis activity or result in depressive-like behaviors during midto-late lactation 27,[70][71][72][73] . Nevertheless, future studies are needed to determine the precise effect of pup removal on early postpartum neuroendocrine activity and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we hypothesize brief periods of pup separation during neuroendocrine and behavioral assays in our study did not significantly contribute to our stress paradigm. Previous studies have shown brief pup separation is not a sufficient stressor to increase maternal HPA axis activity or result in depressive-like behaviors during midto-late lactation 27,[70][71][72][73] . Nevertheless, future studies are needed to determine the precise effect of pup removal on early postpartum neuroendocrine activity and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, poor parental ties are usually associated with increased risk for several psychological vulnerabilities, whereas an increase in parental care improved behavioral outcomes, cognitive performance and also boost resiliency to stress (Canetti et al, 1997;Meaney, 2001;Kaffman and Meaney, 2007). Accordingly, early handling procedure, consisting in a short maternal separation of the mother from the pups, represents a particular event for the dam that is able to produce higher level of interest by the mother in the offspring and, in turn, elicits more maternal care upon reunion (Rees and Fleming, 2001;Kosten and Kehoe, 2010;Zimmerberg and Sageser, 2011;Own and Patel, 2013;Orso et al, 2018). These observations are consistent with those obtained in the present research where the effects on the maternal-infant dyad were investigated.…”
Section: Effects Of Early Brief Maternal Separationmentioning
confidence: 99%
“…Las madres no separadas en los primeros días mostraban un comportamiento maternal alto, pero este iba disminuyendo; en cambio, las madres separadas primero mostraban un comportamiento maternal bajo que aumentaba con el paso de los días. Esta evaluación del comportamiento maternal se llevó a cabo durante 6 días con un total de 18 observaciones (Orso et al 2018). Discusión La influencia del estrés en la conducta maternal es un campo que precisa mayor investigación, pues mucho es sabido sobre el efecto que provoca el estrés en las primeras etapas de la vida de las crías y en su posterior desarrollo adulto, pero mucha menos investigación existe hasta la fecha sobre el efecto que el estrés produce en el circuito neural que induce la conducta maternal.…”
Section: Estrés Social/emocionalunclassified
“…Por último, y siendo el dato más novedoso y relevante para nuestro estudio, se ha observado que la separación materno-filial provoca cambios en el patrón comportamental de las madres, ya que las madres que han sido separadas de sus crías muestran un patrón de cuidado mucho más ansioso, siendo sobreprotectoras a lo largo del tiempo, algo que no se observa en madres no separadas (Orso et al 2018). En ratas, se ha demostrado que la maternidad provoca cambios en la expresión de CRF cerebral provocando que las madres presenten una mejor respuesta al estrés, bajada de ansiedad y control del miedo (Stern, Goldman y Levine 1973; Bitran, Hilvers y Kellogg 1991), tratándose de una respuesta totalmente adaptativa para llevar a cabo la crianza.…”
Section: Estrés Social/emocionalunclassified
See 1 more Smart Citation